Hermes/Mercury Depictions on Anatolian Glyptics - Laflı, Ergün; Henig, Martin (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
The study conducts an iconographic analysis of Hermes/Mercury representations on gems discovered in Anatolia and preserved in the local museums of modern Turkey. The aim is to compile an iconographic corpus primarily of “Fundgemmen” on which Hermes is the main or only figure. Most of the gems presented here date from the second and third centuries AD. The research examines a total of 31 gems, which the authors classify into seven distinct types. Their final conclusion indicates that while certain types exhibit specific characteristics, no distinctly Anatolian representation type can be established. So interesting working on a type that iconographically is so similar over the Empire though doubtless had many local characteristics and names.